PENERAPAN INFOGRAFIS LEGENDA PUTRI AYU LIMBASARI BERBASIS PROBLEM-BASED LEARNING PADA PEMAHAMAN MENYIMAK TEKS AURAL SISWA KELAS VI SDN 2 KUTAWIS PURBALINGGA - Dinar Octari; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop and implement a culture-based digital flipbook integrated with the Problem-Based Learning (PBL) model to improve sixth-grade students’ critical thinking skills and listening comprehension of aural texts at SDN 2 Kutawis, Purbalingga. The study was conducted to address the issue of low student engagement and comprehension in listening activities due to the lack of interactive and culturally relevant learning media. This research employed a mixed-method approach combining quantitative methods to measure the improvement of students’ learning outcomes and qualitative methods to analyze students’ learning responses. The instruments included listening comprehension tests, critical attitude observation sheets, and interviews with students and teachers. The results showed that integrating local cultural values into the flipbook effectively enhanced students’ understanding of literal and implied meanings in spoken texts. Moreover, the implementation of the PBL model through flipbook media increased students’ motivation, participation, and critical reflection during learning. This study contributes to the development of interactive and culture-based digital learning media that support innovative and meaningful Indonesian language learning in elementary schools.